Harmonis Learning Model That Integrates Multiculturalism Into Local History Education - Deny Yudo Wahyudi; Daya Negri Wijaya; Andhika Yudha Pratama; Shela Dwi Utari (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The development of a culturally responsive teaching model, commonly called the Aligned Learning Model, is based on the idea that students' cultural backgrounds are significant in their learning process. Multicultural awareness in history education is an important aspect of education that aims to foster understanding and appreciation of cultural diversity. Integrating multicultural values into history education is essential for raising students' awareness of cultural pluralism and fostering tolerance and social cohesion attitudes. Methodology: In this study, we used a qualitative approach, distributing questionnaires to history teachers to collect data. We analysed the data in three stages: data reduction, presentation, and conclusion drawing. Main Findings: The result of this study is a new learning model called Harmonis. The syntax of this model consists of five stages: learning instruction, concrete experience, reflection, communication, and evaluation. Based on the study's results, previous studies and findings in the field indicate that no specific model elaborates on local history and multicultural education in schools. This prompted the researchers to present an innovation, namely the Harmonis learning model. The Harmonis model can be applied in local history-based learning processes by exploring the surrounding environment and identifying multicultural values that can be taught to students. Novelty/Originality of this study: The Harmonis model bridges the needs of prospective professional teachers who want to teach multiculturalism contextually. The existence of this model is an innovation because several previous learning models have not been able to integrate local history and multiculturalism in a meaningful way.